EFFECTIVENESS OF ORAL ISOTRETINOIN VERSUS TOPICAL TRETINOIN 0.05% IN THE MANAGEMENT OF FACIAL PLANE WARTS - Khan, Jahangir; Gul, Huma; Ullah, Irfan; Khan, Mehran; Jamil, Zarar Bin; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2025)
Background: Facial plane warts present a therapeutic challenge due to limited treatment options. Electrocautery and cryotherapy, though effective, carry risks of scarring and pigmentation. LASER therapy is often inaccessible in resource-limited settings. While both topical tretinoin and oral isotretinoin have shown satisfactory outcomes, no standard treatment exists. Dermatologists are cautious with oral isotretinoin due to the absence of clear guidelines. This trial aimed to compare the efficacy of oral isotretinoin versus topical tretinoin 0.05% in treating facial plane warts. Methods: Approved by the hospital’s ethics board, the study began in January 2023 at Khyber Teaching Hospital. Clinically diagnosed patients with facial and neck plane warts were enrolled. A total of 106 participants were randomized into two groups. Group A received topical tretinoin 0.05%, while Group B was administered oral isotretinoin at 0.5 mg/kg. Treatment response was assessed at 1 and 3 months. Complete lesion clearance marked treatment success, with monthly follow-up for 3 months to assess recurrence. Results: Among 106 patients (61 males, 45 females), 30 (56.6%) in Group A and 42 (79.2%) in Group B achieved complete clearance (p=0.0125). Recurrence occurred in 4 participants per group (13.3% in A; 9.3% in B, p=0.612). Conclusion: Oral isotretinoin proved significantly more effective than topical tretinoin 0.05% in treating facial plane warts, with a comparable recurrence rate.